2007
DOI: 10.1111/j.1365-2222.2007.02815.x
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of type 1a angiotensin II receptors in the regulation of airway inflammation in a murine model of allergic asthma

Abstract: AT1a might be involved in the negative regulation of the development of allergic airway inflammation through polarizing the T-helper (Th) balance towards Th1 predominance. Therefore, it would be of clinical importance to investigate the effects of long-term administration of AT1 blockers on the Th1/Th2 balance in hypertensive patients with bronchial asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…Knockout mice for the AT 1 R gene that were sensitized to ovalbumin and then exposed to ovalbumin inhalation developed a much more intense Th2 response, eosinophilic accumulation and greater concentrations of Th2-specific cytokines such as IL-4, IL-5 and IL-13 in their bronchial tissues than did their wild-type controls [58]. AngII polar- Adrenal gland synthe zises aldosterone izes the Th1/Th2 balance in favor of Th1 in experimental models of autoimmune diseases such as experimental autoimmune encephalomyelitis (EAE), a well-established mouse model for human multiple sclerosis, experimental autoimmune uveitis and myocarditis, whereas ACE inhibitors and AngII receptor blockers have the opposite effect [59,60].…”
Section: Angii and Inflammatory Cellsmentioning
confidence: 96%
“…Knockout mice for the AT 1 R gene that were sensitized to ovalbumin and then exposed to ovalbumin inhalation developed a much more intense Th2 response, eosinophilic accumulation and greater concentrations of Th2-specific cytokines such as IL-4, IL-5 and IL-13 in their bronchial tissues than did their wild-type controls [58]. AngII polar- Adrenal gland synthe zises aldosterone izes the Th1/Th2 balance in favor of Th1 in experimental models of autoimmune diseases such as experimental autoimmune encephalomyelitis (EAE), a well-established mouse model for human multiple sclerosis, experimental autoimmune uveitis and myocarditis, whereas ACE inhibitors and AngII receptor blockers have the opposite effect [59,60].…”
Section: Angii and Inflammatory Cellsmentioning
confidence: 96%
“…Th1 cells were positively associated with various cardiovascular diseases [3]. Currently, it has been demonstrated that many factors can regulate T cell differentiation toward the Th1 or the Th2 phenotype including T-box expressed in T cells (T-bet) and (GATA3) T-bet is a‘master regulator’of Th1 cell development, while GATA3 is a key T-cell transcription factor to regulate Th2 T-cell differentiation [4], Recently, Ang II-mediated signalling has been reported to play a critical role in Th differentiation [5]. However, the precise mechanism by which Ang II promotes Th1 differentiation remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Serum levels of OVA-specific IgE on day 37 before the second challenge were measured with ELISA, as described previously [32]. …”
Section: Methodsmentioning
confidence: 99%